2004
DOI: 10.1159/000082527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Androgens on Sexual Differentiation of Pituitary Gamma-Aminobutyric Acid Receptor Subunit GABA<sub>B</sub> Expression

Abstract: Previous work demonstrated a sexually dimorphic ontogenic expression of γ-aminobutyric acid receptors (GABABR) in rat pituitary. As sex steroids determine sex-specific expression patterns, we now studied the effect of sex hormones on pituitary GABABR expression. GABABR subunits, measured by Western blot and by semi-quantitative RT-PCR and luteinizing hormone (LH), follicle-stimulating hormone (FSH) and testosterone measured by RIA were determined in two experimental designs: Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 137 publications
3
22
0
Order By: Relevance
“…Functional GABA B Rs are obligate heterodimers composed of a GABA B1 and a GABA B2 subunit (12,48). In this regard, we showed that GABA B R subunits have particular ontogenic expression patterns in the rat hypothalamus and the pituitary (9,10) and that their expressions show sexual dimorphisms at early stages of development (8,9). In GABA B1 knockout (GABA B1 KO) mice, which lack functional GABA B Rs (79), we demonstrated that GABA B Rs are involved in regulating basal prolactin (PRL) release in males and that the hypothalamic-hypophyseal-ovarian axis is compromised in females, with significant alterations in cyclicity, postcastration LH increase, and reproduction indexes (14).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Functional GABA B Rs are obligate heterodimers composed of a GABA B1 and a GABA B2 subunit (12,48). In this regard, we showed that GABA B R subunits have particular ontogenic expression patterns in the rat hypothalamus and the pituitary (9,10) and that their expressions show sexual dimorphisms at early stages of development (8,9). In GABA B1 knockout (GABA B1 KO) mice, which lack functional GABA B Rs (79), we demonstrated that GABA B Rs are involved in regulating basal prolactin (PRL) release in males and that the hypothalamic-hypophyseal-ovarian axis is compromised in females, with significant alterations in cyclicity, postcastration LH increase, and reproduction indexes (14).…”
mentioning
confidence: 82%
“…The anterior limit of the fragments was a plane at the height of the anterior commissure, lateral limits were the hypothalamic fissures, the posterior limit was behind the mammilary bodies, and the in-depth limit was the subthalamic sulcus, as previously described (8). The olfactory bulbs (OB) and frontoparietal cortex (CT) were also rapidly dissected and frozen.…”
Section: Gnrh Content Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were divided into five groups (n ϭ 12/group): hypothyroid, (0.02% methimazole (w/v) in drinking water for 28 days); hypothyroidϩT 3 , (after 25 days of methimazole treatment received 15 g of T 3 /kg of body weight for 3 days by intraperitoneal injection); hypothyroidϩL-NAME, (0.75 mg/ml L-NAME in drinking water in the last 21 days of methimazole treatment); hyperthyroid, (intraperitoneal injection of 60 g of T 3 /kg of body weight for 3 days); and control group. Blood samples were collected at the time the animals were killed for estimation of thyrotropin (TSH) level by radioimmunoassay (20).…”
Section: Methodsmentioning
confidence: 99%
“…Results from our laboratory [18, 19] established that GABA B R subunits have particular ontogenic expression patterns in hypothalamus and pituitary, decreasing throughout postnatal development in both sexes and being more abundant in female than in male infantile rats. This dimorphic sexual expression pattern in the pituitary is the consequence of early testosterone imprinting in males [20]. In addition, we have demonstrated [21] that pituitary GABA B Rs are coupled Gi/0-type G-proteins and that their activation initiates the same intracellular signaling pathways as in the CNS.…”
Section: Introductionmentioning
confidence: 99%